‘Why Was He Videoing Us?’: The ethics and politics of audio-visual propaganda in child trafficking and human trafficking campaigns - Okyere, Sam; Agyeman, Nana; Saboro, Emmanuel (Anti-Trafficking Review, 2021)
This paper is a critical reflection on the ethical and political issues associated with the creation and dissemination of unsettling images and videos for child trafficking and human trafficking abolitionist campaigns. The paper acknowledges efforts by anti-trafficking campaigners to address accusations of poverty porn, stigmatisation, and sensationalism directed at such visual propaganda. However, it also observes that these remedial measures have had very little impact. Anti-child trafficking and anti-human trafficking campaigns are still dominated by sensational spectacles of victimhood, abjection, pain, and suffering. The paper attributes this inertia to campaigners’ fears that radical deviation from the use of emotive or ‘biting’ visuals may undermine their established narratives, campaign goals, and even credibility. It supports this conclusion using path dependence theory and the findings of research with residents of remote island communities on the Lake Volta in Ghana who have been the focus of extensive anti-child-trafficking raids and campaigns over the last decade.